Tools of the crook‐ infection strategies of fungal plant pathogens. (29th January 2018) - Rodriguez‐Moreno, Luis; Ebert, Malaika K.; Bolton, Melvin D.; Thomma, Bart P.H.J.
Summary: Fungi represent an ecologically diverse group of microorganisms that includes plant pathogenic species able to cause considerable yield loses in crop production systems worldwide. In order to establish compatible interactions with their hosts, pathogenic fungi rely on the secretion of molecules of diverse nature during host colonization to modulate host physiology, manipulate other environmental factors or provide self‐defence. These molecules, collectively known as effectors, are typically small secreted cysteine‐rich proteins, but may also comprise secondary metabolites and sRNAs. Here, we discuss the most common strategies that fungal plant pathogens employ to subvert their host plants in order to successfully complete their life cycle and secure the release of abundant viable progeny. Significance Statement: Fungal pathogens cause considerable yield loses in crop production systems worldwide. We discuss the most common strategies that fungal plant pathogens employ to subvert their host plants in order to successfully complete their life cycle and secure the release of abundant viable progeny.